The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1074/jbc.271.10.5704
|View full text |Cite
|
Sign up to set email alerts
|

A Conditional Lethal Mutant in the Fission Yeast 26 S Protease Subunit mts3+ Is Defective in Metaphase to Anaphase Transition

Abstract: We have isolated a conditional lethal mutant mts3 in the fission yeast Schizosaccharomyces pombe which at the permissive temperature is resistant to the mitotic poison MBC and at the restrictive temperature is defective in metaphase to anaphase transition. The predicted amino acid sequence of mts3 ؉ is 36% identical with the budding yeast gene NIN1. NIN1 cloned into a fission yeast expression vector can rescue both mts3 temperature-sensitive and null alleles demonstrating that NIN1 is the budding yeast homolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
107
1
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 32 publications
3
107
1
1
Order By: Relevance
“…Flow Cytometry-Flow cytometry was carried out using a Becton Dickinson FACScan using the method described previously (10,21).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Flow Cytometry-Flow cytometry was carried out using a Becton Dickinson FACScan using the method described previously (10,21).…”
Section: Methodsmentioning
confidence: 99%
“…In the presence of ATP, the 19 S cap binds to each end of the 20 S core and confers ATP dependence and specificity for ubiquitinated substrates on the 26 S complex (7). The budding yeast SUG1 gene (8) and the fission yeast mts2 ϩ gene (9) are known to encode ATPase components of the 19 S cap, while the fission yeast mts3 ϩ and mts4 ϩ genes encode non-ATPase subunits (10,11). At the restrictive temperature the phenotypes of the temperature-sensitive (ts) 1 mts2-1 and mts3-1 strains are transient cell cycle arrest at metaphase, indicating that the metaphase to anaphase transition is blocked (9,10).…”
Section: And 4)mentioning
confidence: 99%
See 1 more Smart Citation
“…It binds Cut9 directly and is required to link different APC/C subcomplexes together. We have mapped the single site of phosphorylation within Hcn1 to Ser 48 , a consensus site for Cdk1. Mutational analysis indicated that Hcn1 phosphorylation is not an essential modification, but mutation of Ser 48 to alanine induced a novel S. pombe APC/C phenotype.…”
mentioning
confidence: 99%
“…We followed the levels of all three CAK subunits in Skp1 (skp1-3 [40]) or proteasome (mts3-1 [51]) temperature sensitive mutants, where known targets (Cdc18 and Cig2) of SCF-mediated ubiquitinylation and proteolysis accumulate at the restrictive temperature [52][53][54][55]. Total levels of HA-Mcs2, Pmh1-TAP, and Mcs6-TAP were followed by Western blot (anti-Ha or PAP; see Materials and methods) in wild type, skp1-3 or mts3-1 mutant strains after shift to restrictive temperature (Figs.…”
Section: Fission Yeast Cak Regulation By Proteasomedependent Proteolysismentioning
confidence: 99%